ChemInform Abstract: Silver(I)‐Mediated Coupling Reaction of Heterocyclic Ketene Aminals (HKAs) with Bis(phenylsulfonyl)sulfides to Synthesis of Benzenesulfonothioyl‐HKAs. Issue 13 (March 2015) - Liu, Ting‐Ting; Lin, Xin‐Rong; Huang, Rong; Yang, Li‐Fen; Yan, Sheng‐Jiao; Lin, Jun
Abstract The products are prepared in view of new anticancer drugs.